Ethics Politic Kari Palonen of Weberian Perspective - Elfi, Elfi; Tri Hadi, Rahmad (Politeia: Jurnal Ilmu Politik, 2024)
This study aims to describe and analyze the political ethics of Kari Palonen's thoughts. The method used in this study is a descriptive-analytical method with a Weberian approach. The primary data used in this research is the works of Kari Palonen himself. While the secondary data in this study are books, journal articles, and other websites that discuss Kari Palonen's thoughts. The results of the study show that political ethics in Kari Palonen's perspective includes five dimensions, viz political (political action), polity (facilities; institutions), policy (policy; purpose), politicking (political activity), and politicisation. The five elements in the Weberian perspective constitute a scope of complexity that cannot be separated and are interrelated in forming and understanding a country's political ethics.